Kajian Budaya Dan Potensi Kearifan Lokal Di Gunung Limo Sebagai Ikon Wisata Budaya Pacitan - Arif Puja Pangestu; Yusuf Adam Hilman (Jurnal Pemerintahan dan Politik, 2020)
Many local wealth and wisdom are found in various areas, one of Indonesia's potential assets. Both government and community, both have similar ownership status and future goals. One local wisdom is the culture and customs stored in Gunung Limo, right in the village of mantren district pacitan. It is a land of history and is rife with folk activities closely associated with traditional beliefs, beliefs, and customs. The study seeks to assess local prudence potential with an object mountain, then be correlated with the prospect of developing cultural tourism by the government. This is because pacitan is an area identical to the tourist sector in the eyes of both local and foreign tourists. The government has the opportunity and the power to increase existing funding as well as to increase the welfare of the people around it. Gunung Limo itself has proved to be of historic value and unique local civilization, but neither the government can be sure of its planning nor the focus of future development. Therefore, the study also dug up scientific information from different literature sources to refer to formulating concepts, ideas, and ideas for the Gunung Limo as cultural tourist icons in pacts. The potential for Gunung Limo asa future tourist destination, a promising guarantee for the economic growth of the people around, as well as the country's income automatically.Keywords : Potensi, Kearifan Lokal, Gunung Limo, Wisata Budaya, Pacitan